β-Grain refinement in WAAM Ti-6Al-4 V processed with inter-pass ultrasonic impact peening - Sahu, Vivek K.; Biswal, Romali; Davis, Alec E.; Chen, Xin; Williams, Stewart W.; Prangnell, Philip B. (Elsevier, 2024)
As-deposited Wire-Arc Additive Manufactured (WAAM) Ti-6Al-4V parts typically contain large columnar β-grains on a centimetre scale, with a strong 〈001〉 fibre texture, leading to anisotropic mechanical properties and unacceptable scatter in damage tolerance. Inter-pass deformation, introduced by the application of Ultrasonic Impact Peening (UIP) across each added layer, has been shown to be effective in refining the β-grain structure and achieving a weaker texture. The depth of deformation and the grain refinement mechanism induced by UIP have been investigated by combining advanced electron backscatter diffraction (EBSD) characterization with a ‘stop action’ observation technique. UIP facilitates a similar refinement mechanism and nearly the same depth of deformation as conventional machine hammer peening, with the advantages of a much higher strain rate, lower peak force, and two orders of magnitude lower impact energy, making it a faster and more economical process. β recrystallization is seen within the deformation zone during re-heating through the α → β transition. Although new recrystallized β-grains formed in the UIP surface-deformed layer to a shallower depth than that of remelting, recrystallization initiated ahead of the melt pool and the recrystallized grains grew downwards to a greater depth before remelting. These refined grains were thus able to survive and act as nucleation sites at the fusion boundary for epitaxial regrowth during solidification, greatly refining the grain structure.
Keywords: Ultrasonic impact peening; Wire-arc additive manufacturing; Titanium alloys; Beta grain refinement; Large area EBSD large area EBSD; 40 Engineering; 4016 Materials Engineering; 3403 Macromolecular and materials chemistry